PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SIGI - Fadlan, Fadlan (Katalogis, 2015)
The reesearch aims to analyze simultanneous and partial impacts of competency, motivation, discipline and working environment on employees’ performance in The of Social Service, Labor, and Transmigration, Sigi Regency. The respondents consisit of 41 employees of the Office of Social Service, Labor, and Transmigration, Sigi Regency. Method of analysis used is multiple linear regression. The result concludes that competency, motivation, discipline and working environment simultaneuosly and partially have impacts on employees’ performance in The Office of Social Servive, Labor, And Transmigration, Sigi Regency.